The Double-Edged Sword: Government Officials' Perceptions of AI and its Impact on Efficiency, Accountability, and Transparency - Kanayo Chike Nwosu; Chinedu Eke; Chinedu Francis Egbunike; Daniel Izuchukwu Chude; Nkiru Patricia Chude (Cigarskruie: Journal of Educational and Islamic Research, 2025)
Artificial Intelligence (AI) is increasingly transforming governance by enhancing efficiency, accountability, and transparency in public administration. This study explores MDAs employees' perceptions of AI's impact on efficiency, accountability, and transparency in public administration. The study adopted a survey research design. A sample of 300 government employees was surveyed, and the data were analyzed using Pearson correlation and simple linear regression. The results showed that AI significantly enhances government efficiency (r = .765, p < 0.05), accountability (r = .653, p < 0.05), and transparency (r = .776, p < 0.05). Despite these benefits, challenges such as algorithmic bias, regulatory gaps, and data privacy concerns persist. The employees also identified the need for regulatory frameworks, ethical governance, and periodic investment in training to ensure responsible AI use. However, strengthening institutional capacities and fostering public trust through transparency measures are critical for AI's effective implementation in governance. The study contributes to the ongoing discourse on AI’s role in governance and administration with empirical findings to inform policy development and governance reforms. Addressing identified barriers will be essential for maximizing AI’s potential while ensuring equitable and accountable governance practices.